Control of slewing motions of flexible structures using shape memory alloy - Janzen, Frederic C. [UNESP]; Tusset, Ângelo M.; Piccirillo, Vinicius; Balthazar, José M. [UNESP]; De Pontes, Bento R. [UNESP]; Silveira, Marcos [UNESP]; Brasil, Reyolando M.L.R.F. (ASME International, 2014)
This paper presents the position and vibration control of a single flexible slewing structure driven by a DC motor at the slewing axis. The position is controlled over the current applied to the DC motor armature. To control the vibration of the flexible structure Shape Memory Alloys (SMA) are applied to them. The control is made through the State Dependent Ricatti Equations (SDRE) technique which uses sub-optimal control and system local stability search. Numerical simulations and experimental results are presented which demonstrate the effectiveness of the proposed control strategy.